PERANCANGAN SISTEM INFORMASI LOGBOOK KEGIATAN AKADEMIK BERBASIS WEBSITE - Gitarja Sandi; Adi Surya Widura; Eka Amelia (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Website is one of the internet media that is often used to do many useful things, including facilitating registration. Previously, Faculty of Engineering University Islam Nusantara still did manual recording of academic data. These academic activities include teaching and learning activities, real exercises, practical work and other academic activities. Seeing such things, there is a need to build a log information system project that can input data from the offline system to the website system that aims to manage and store the data using the website and a build system that can facilitate the performance of the teacher and the teacher. Administrative staff of the Faculty of Engineering, University Islam Nusantara. The website-based logging system has the advantage of convenient use, clearly stored data, more structured data, and easier data logging. The tools used in the development of this system are PHP and MySQL. This research has resulted in an academic registry system that is easily accessible to various related parties of the Faculty of Engineering, University Islam Nusantara, including structured registration, archiving and reporting